Penerapan Birth Ball Exercise Terhadap Kontrol Nyeri pada Asuhan Keperawatan Ibu Intranatal Care Kala I di Puskesmas Kayamanya - Nurul Aulia Putri Ningsih; Nirva Rantesigi; Dewi Nurviana Suharto (Madago Nursing Journal, 2022)
Introduction : Labor and birth are normal physiological events. First stage of labor (opening stage) begins when there are regular contractions and increases until complete dilatation. One of the problems that arise in childbirth is pain. So, because of these conditions, it is necessary to intervene to control pain by giving birth ball exercise therapy. For the application of intranatal care for mothers with the first stage at the Kayamanya Public Health Center. The measuring instrument used to measure pain is the Visual Analog Scale (VAS). Method : Research Method That is using descriptive method with case study approach. Result : The results showed that birth ball exercise can control labor in first stage intranatal care mothers. The application of birth ball exercise can control labor pain in 1st stage of intranatal nursing care. Conculsion : It is expected that patients can perform birth exercises independently according to what has been taught by researchers..